2019
DOI: 10.21608/ejnf.2019.102283
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Partial Replacement of Cottonseed Meal by Nigella Sativa Meal on Nutrients Digestibility, Rumen Fermentation, Blood Parameters, Growth Performance of Growing Lambs

Abstract: his study was conducted to evaluate the effect of partial replacement of cotton seed meal in concentrate mixture by Nigella sativa (N. sativa) meal on nutrients digestibility, rumen fermentation, blood metabolites and performance of lambs. Eighteen of healthy Farafra male lambs aged between 5 and 6 months old and had average of 27.2 ± 1.3 kg body weights. The lambs were randomly assigned into three groups, 6 animals each lasted for 90 days. The experimental groups were a control group (CON) fed basal diet cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…Significant improvement in nutritive values as DCP was associated with increasing the digestibility coefficients of CP. Similar trends were obtained by the investigation of (Salem et al, 2001). Also, Yahia et al (2018) showed that the improvement in nutritional values as seen in TDN and DCP reflects the positive effect of dietary supplementation with 200 g tafla/h/d on the digestibility coefficients of most nutrients when compared with the control diet.…”
Section: Nutrient Digestibility and Nutritive Valuessupporting
confidence: 81%
See 2 more Smart Citations
“…Significant improvement in nutritive values as DCP was associated with increasing the digestibility coefficients of CP. Similar trends were obtained by the investigation of (Salem et al, 2001). Also, Yahia et al (2018) showed that the improvement in nutritional values as seen in TDN and DCP reflects the positive effect of dietary supplementation with 200 g tafla/h/d on the digestibility coefficients of most nutrients when compared with the control diet.…”
Section: Nutrient Digestibility and Nutritive Valuessupporting
confidence: 81%
“…One of the more popular feed additives used by commercial dairies in ruminant diets is clay minerals. This additive decreases the passage rate of the digesta through the digestive tracts, enhancing digestion efficiency and, as a result, increasing feed utilization (Salem et al, 2001). Clay minerals mainly hydrate include aluminum silicate (brucite), kaolinite, montmorillonite, illite, chlorite, sepiolite, bentonite, zeolite, and hydrated sodium calcium aluminosilicate (Eng et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research shown that supplementation of (1.0) to (1.3) g DM of Planatago lanceolata L. (plantain) and Allium sativum (garlic leaf) per kg of live body weight of lambs fed with pellets (total mixed ration TMR) or (mixed hay) led to improve lambs production (43,46). Moreover, addition of N. sativa meal until rate 66.7% as alternative source for cotton seed meal in diets of sheep may recommend improving feed utilization and growth performance of growing Farafra sheep (47).…”
Section: Volmentioning
confidence: 99%
“…All antioxidants in spices and herbs are very effective because they possess excellent antioxidant activity (21). Another study found that adding 4g Roselle /kg DM and/or 4g Lemongrass/ kg DM were significantly increased total antioxidant capacity in treated ewes compared to untreated ewes (47). Adding supplement of turmeric, vitamin and Andrographis paniculata to the diets, it was discovered that meat from supplemented goats had greater antioxidant activities and sensory quality has been improved when they compare antioxidant contents in meat (52).…”
Section: Vol 14mentioning
confidence: 99%